Epigenetic changes in the estrogen receptor α gene promoter: implications in sociosexual behaviors - Matsuda, Ken Ichi (Frontiers in Neuroscience, 2014)
Estrogen action through estrogen receptor α (ERα) is involved in the control of sexual and social behaviors in adult mammals. Alteration of ERα gene activity mediated by epigenetic mechanisms, such as histone modifications and DNA methylation, in particular brain areas appears to be crucial for determining the extents of these behaviors between the sexes and among individuals within the same sex. This review provides a summary of the epigenetic changes in the ERα gene promoter that correlate with sociosexual behaviors.